Analisis Kemampuan Spasial Siswa Berdasarkan Cognitive Load Theory Siswa Kelas XII SMA N 13 Kota Jambi - Rachmawati, Ira; Sabil, Husni; Junita, Ranisa (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This research aims to describe students spatial abilities based on cognitive load theory in geometry learning. This research approach is a qualitative approach and the type of research is descriptive research. The data obtained in this research includes qualitative data obtained from observation sheets, tests, interviews and documentation. To check the validity of the data using the data triangulation method. The subjects in this research were students of class XII Science 3 SMA Negeri 13 Jambi City. The research results showed that students' spatial abilities were still low and there was a cognitive load on students. The cognitive load that arises in learning can be seen from the complexity of the material studied, media, methods and learning strategies used by the teacher. To improve students' spatial abilities, teachers can design learning with appropriate media, methods and strategies so as to minimize the cognitive load on students.